Multidose Drug Dispensing in Community Healthcare Settings for Patients With Multimorbidity and Polypharmacy - Adela Martín-Oliveros PhD Pharma; Javier Plaza Zamora PhD Pharma; Alessandro Monaco MBA, PhD; Javier Anitua Iriarte MBA, PDG; Jessica Schlageter MA; Danute Ducinskiene MD, PhD; Shaantanu Donde MBBS, MSc, MBA (SAGE Publishing, 2024)
Multidose drug dispensing (MDD) is the dispensing of different drugs in dose bags containing one, some, or all units of medicine that a patient needs to take at specific times. The aim of this narrative review is to provide an overview of the literature describing the use of MDD systems in community healthcare settings in patients with multimorbidity and polypharmacy. A literature search identified 14 studies examining adherence, medication knowledge, quality of drug prescription (including inappropriate drug use, drug-drug interactions), medication incidents, and drug changes after MDD initiation, as well as healthcare professional (HCP) and patient perspectives. There are limited data on MDD in community healthcare settings, particularly on outcomes such as adherence. Studies are mostly from Northern Europe. Patients selected for MDD are more likely to be older, female, cognitively impaired, and have a higher number of disease diagnoses and drugs than those who do not receive drugs through MDD. MDD is generally initiated for patients who have decreased capacity for medication management. Several advantages of MDD have been reported by patients and HCPs, and studies indicate that MDD can be improved by medication review, defining clear roles and responsibilities of HCPs in the medication management chain, and comprehensive follow-up of patients. Future development, implementation, and assessment of MDD systems in community healthcare should be designed in collaboration with HCPs and patients, to identify ways to optimize the systems and improve patient outcomes.